PENGARUH PENILAIAN RESIKO DAN PENGENDALIAN PIUTANG TERHADAP EFEKTIVITAS PENAGIHAN PIUTANG PADA PT CAHAYA MURNI CEMERLANG - Ni Putu Eka Septyanti (UNHI Press, 2022)
The purpose toshow influence risk assessment & control of receivables ineffectiveness of receivables collection at PT Cahaya Murni Cemerlang. The populati inthis stady wereall employee of PT Cahaya Murni Cemerlang, as much 50 employees. The sample used was 43 employees who were determined by purposive sample techniq. The datanalysis used multiplle liniar regresion. Based on the results of the research and discussion that have been described, it can be concluded that the risk assessment variable has a positive and significant effect on the effectiveness of receivables collection. Accounts receivable control have positiv & significan infuence onthe effectiveness of receivables collection.